Juridical Analysis of the Determination of Abandoned Land by the Government on Land Owned by the Community - Wibowo, Hanifah Fairuz; Taupiqqurrahman, Taupiqqurrahman (UNIVERSITAS PAKUAN, 2025)
Abstract The research was conducted to legally analyze the regulations and mechanisms for determining abandoned land by the government for community-owned land and to examine the potential legal impacts arising from this policy. Land has an important position in the lives of Indonesian people, but when land is not utilized according to its intended purpose, the state has the authority to determine it as abandoned land, which is sourced from the provisions of Law Number 5 of 1960 concerning the Basic Agrarian Law, Government Regulation Number 20 of 2021, and Regulation of the Minister of ATR/BPN Number 20 of 2021. This type of research is normative legal research with data collection techniques through library research, the results obtained are that the mechanism for determining abandoned land includes the stages of inventory, evaluation, warning, and determination by the Minister of Agrarian Affairs and Spatial Planning. This policy has a positive impact in realizing equitable control and utilization of land through redistribution and agrarian reform, while supporting national development goals. However, on the other hand, there is the potential for negative impacts such as agrarian conflict, loss of land ownership rights, legal uncertainty, and social unrest if the determination procedure is carried out without regard to the principles of justice and community participation. Therefore, regulations are needed to be more clear, transparent, and equitable so that the implementation of the determination of abandoned land truly reflects legal protection and community welfare. Keywords: Abandoned Land, Property Rights, Agrarian